Tata Kelola Gambaran Perencanaan Media Pembelajaran Berbasis Audio Visual pada Mata Pelajaran Bahasa Indonesia di SMA Negeri 1 Larompong Kabupaten Luwu - Tasdin Tahrim (Institut Agama Islam Negeri (IAIN) Palopo, 2019)
The study aimed to determine the picture of audio visual based learning media planning in Indonesian subjects. This type of research is descriptive qualitative to find the nature or experience of a person with a phenomenon that is the governance of audio visual based learning media. Data was collected through: stakeholder involvement through the planning of Larompong 1 High School learning media management. Audio Visual Based learning media governance is obtained through two data sources namely informants and documents. Data collection techniques through interviews, observation, documentation and focus group discussions. The results of the study show: The governance of audio visual based learning media planning begins with the selection of instructional media tailored to the material and learning objectives in the RPP with the principles of using audio-visual media and refers to the Minimum Completeness Criteria. Students who get the KKM value exceeds the KKM value that has been set by the school means that the student has been able to study thoroughly, conversely if students who get the KKM value is smaller and the KKM value that has been set by the school then the student is said to have not finished learning. Students will be given remedial services by subject teachers and for those who have met the KKM, then given enrichment.